La restauración de las vidrieras de la catedral de Oviedo. De las reformas del Obispo Ramón Martínez Vigil a la intervención de Luis Menéndez Pidal: The restoration of the stained glass windows of the cathedral of Oviedo. From the reforms of Bishop Ramón Martínez Vigil to the intervention of Luis Menéndez Pidal - Cuello Rey, Isaac (Artigrama, 2020)
ResumenLa catedral gótica de Oviedo alberga las vidrieras más antiguas de Asturias. Desde el cierre de sus bóvedas a finales del siglo XV, las vidrieras ubicadas en su claristorio han sufrido pérdidas, añadidos y restauraciones, viéndose condicionadas a lo largo de sus más de quinientos años de historia por diversos factores que van desde la voluntad didáctica del obispo Valeriano Ordóñez de Villaquirán, hasta la búsqueda de una mayor religiosidad de los fieles ante el avance de los movimientos obreros por parte del obispo Ramón Martínez Vigil, o las restauraciones de posguerra de Luis Menéndez Pidal.AbstractThe gothic cathedral of Oviedo houses the oldest stained glass windows in Asturias. Sincethe closure of its vaults at the end of the 15th century, the stained glass windows located in itsclerestory have suffered losses, additions and restorations that have been conditioned throughout its more than five hundred years of history by various factors ranging from didactic willof Bishop Valeriano Ordóñez de Villaquirán, the search for greater religiosity of the faithful intimes of the labor movements of Bishop Ramón Martínez Vigil, or the postwar restorations ofLuis Menéndez Pidal.KeywordsOviedo, Oviedo Cathedral, Stained Glass Windows, Diego de Santillana, Valeriano Ordóñez de Villaquirán, Ramón Martínez Vigil, Santos Cuadrado, Luis Menéndez Pidal.